The Variation and phenetic relationships of Dendrophthoe pentandra (L.) Miq. from various host trees based on morphological characters - Novario Permata Adiansyah; Putri Dian Islami; Purnomo Purnomo (Biogenesis: Jurnal Ilmiah Biologi, 2023)
Dendrophthoe pentandra (L.) Miq.; Loranthaceae) is a shrub parasitic on various host tree species. This species is often used for herbal medicinal ingredients by local communities based on the spesies of host tree. The morphological characteristics of D. pentandra are important to study because their adaptation to different host trees may resulting population of ecotypes. This study aims to determine the variation of D. pentandra accession characters on different host tree species based on morphological characters and to determine morphological phenetic relationships between accessions. Besides studies of D. pentandra accessions in Yogyakarta Province have never been conducted in full. Sample collection (accession) of D. pentandra was conducted for various host tree species from various locations, including roots, stems, leaves, flowers, and fruit. Morphological characterization and scoring of each accession were conducted to create a similarity matrix using the Jaccard Coefficient formula. Based on the similarity matrix between OTUs and the UPGMA algorithm, it can be formed into a dendrogram. The results showed that the morphological variations of D. pentandra were found in phyllotaxis, leaf thickness, petiole length, number of stomata density per field of view, flower color, crown tube length, corolla lobe length, petal length, stamen : corolla lobe ratio, fruit color, and seed color. The population of D. pentandra in Yogyakarta can be divided into two groups, D. pentandra which has alternate and opposite arrangements in phyllotaxis. The accession dendrogram of D. pentandra in Yogyakarta was divided into five clusters starting from a similarity index of 0.089 to 0.952. Thus, the diversity of morphological variations of D. pentandra on host trees is high.